Droplet digital PCR and mile‐post analysis for the detection of F8 int1h inversions. (17th January 2021) - Manderstedt, Eric; Lind‐Halldén, Christina; Ljung, Rolf; Astermark, Jan; Halldén, Christer
Abstract: Background: F8 int1h inversions (Inv1) are detected in 1%–2% of severe hemophilia A (HA) patients. Long‐range polymerase chain reaction (PCR) and inverse‐shifting PCR have been used to diagnose these inversions. Objectives: To design and validate a sensitive and robust assay for detection of F8 Inv1 inversions. Methods: Archival DNA samples were investigated using mile‐post assays and droplet digital PCR. Results: Milepost assays for Inv1 showing high specificities and sensitivities were designed and optimized. Analysis of four patients, two carrier mothers, and 40 healthy controls showed concordance with known mutation status with one exception. One patient had a duplication involving exons 2–22 of the F8 gene instead of an Inv1 mutation. DNA mixtures with different proportions of wild‐type and Inv1 DNA correlated well with the observed relative linkage for both wild type and Inv1 assays and estimated the limit of detection of these assays to 2% of the rare chromosome. Conclusions: The milepost strategy has several inherent control systems. The absolute counting of target molecules by both assays enables determination of template quantity, detection of copy number variants, and rare variants occurring in primer and probe annealing sites and estimation of DNA integrity through the observed linkage. The presented Inv1 milepost analysis offers sensitive and robust detection and quantification of the F8 int1h inversions and other rearrangements involving intron 1 in patients and their mothers.